2018
DOI: 10.1002/adhm.201800315
|View full text |Cite
|
Sign up to set email alerts
|

Functional Multichannel Poly(Propylene Fumarate)‐Collagen Scaffold with Collagen‐Binding Neurotrophic Factor 3 Promotes Neural Regeneration After Transected Spinal Cord Injury

Abstract: Many factors contribute to the poor axonal regrowth and ineffective functional recovery after spinal cord injury (SCI). Biomaterials have been used for SCI repair by promoting bridge formation and reconnecting the neural tissue at the lesion site. The mechanical properties of biomaterials are critical for successful design to ensure the stable support as soon as possible when compressed by the surrounding spine and musculature. Poly(propylene fumarate) (PPF) scaffolds with high mechanical strength have been sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 65 publications
0
49
0
Order By: Relevance
“…The major limitation of PPF is its viscous liquid at room temperature that, in turn, is resulted in cumbersome handling of this polymer. The unique properties of PPF-based Polymers such as biocompatibility, absorbability, injectability, and biodegradability provide the possibility for their extensive usages in biomedicine fields such as scaffolds for tissue regeneration and controlled nanodrug delivery system, preparation of orthopaedic implants and nano-vehicles for cell transplantation [80].…”
Section: Poly (Propylene Fumarate) (Ppf)mentioning
confidence: 99%
See 1 more Smart Citation
“…The major limitation of PPF is its viscous liquid at room temperature that, in turn, is resulted in cumbersome handling of this polymer. The unique properties of PPF-based Polymers such as biocompatibility, absorbability, injectability, and biodegradability provide the possibility for their extensive usages in biomedicine fields such as scaffolds for tissue regeneration and controlled nanodrug delivery system, preparation of orthopaedic implants and nano-vehicles for cell transplantation [80].…”
Section: Poly (Propylene Fumarate) (Ppf)mentioning
confidence: 99%
“…To illustrate this concept, Chen et al combined PPF with collagen biomaterial to provide biocompatible scaffold with high mechanical strength and minimum deformation in a short period compared to collagen alone. They observed that multichannel PPF-Collagen scaffold with collagen-binding neurotrophic factor 3 provides more efficient regrowth-supportive microenvironment for guiding neural tissue regeneration and inhibition of fibrotic scar formation following SCI compared to control, PPF and PPF-Collagen groups (Figure 8) [80].…”
Section: Pcl Polymermentioning
confidence: 99%
“…Copolymerization with PEG has been one popular approach [134], while surface functionalization with peptides also improves cell attachment, allowing applications in drug delivery and cell culturing [120]. Other functional coatings include arginine-glycine-aspartate peptides to support proliferation of human chondrocytes for cartilage tissue engineering [124,135], as well as PPF scaffolds loaded with collagen and coated with neurotrophin-3 to promote bioactivity and specifically the growth and proliferation of neurons and axons [136]. Apart from offering structural support and pores for neuronal regrowth, the stiff PPF scaffold also provided mechanical cues guiding cells to grow in specific directions [136].…”
Section: Bioactivitymentioning
confidence: 99%
“…PCL (4. Human chondrocytes for cartilage tissue engineering [124,135]; Neurotrophin-3 for neurons and axons [136]; Adipose stem cell adhesion for tissue regeneration [137];…”
Section: Sls (31) Fdm (32) Extrusion Bioprinting (33) Light-assistmentioning
confidence: 99%
“…Diverse neurotrophic factors have contributed to the poor axonal regrowth and ineffective functional recovery in the SCI repair process (Chen et al, 2018a,2018b; Mesentier‐Louro et al, 2019). It has been reported that glial cell line‐derived neurotrophic factor (GDNF) has protective potential in neurodegeneration disease(Mukhamedshina et al, 2016).…”
Section: Sustained Release Of Neurotrophic Factors By Chitosan Complementioning
confidence: 99%